A aplicação do instituto jurídico das “situações excepcionalíssimas” do HC 143.641 (STF) no âmbito do Tribunal de Justiça da Paraíba: uma análise à luz da criminologia feminista - Albuquerque, Willana Alves de (2022)
The Second Panel of the Federal Supreme Court of Brazil determined, in February 2018, in the judgment of Collective Habeas Corpus nº 143.641/SP, that all women subject to precautionary arrest who are pregnant, that have recently given birth or that are mothers of children up to 12 years of age or a of person with any kind of disability have the right to have replaced the preventive detention that has been imposed on them by house arrest. However, some exceptions were made to the enjoyment of this right: the commission of the crime through violence or serious threat; the finding that the accused's own descendants were the victims of the crime; or the occurrence of "extremely exceptional situations", capable of justifying the continuation of the most restrictive measure, which should be duly outlined and justified by the judges who raise them. This dissertation relates, therefore, as the object of study, precisely the jurisprudentially established exception of the institute of “exceptional situations”, which do not have their meaning sufficiently predefined. From the relative opening of the meaning of this legal institute, the following research problem is extracted: “what are the arguments that support the interpretations of the meanings allegedly attributed by the magistrates working in the Criminal Chamber of the Court of Justice of the State of Paraíba, in Brazil, to the institute of 'extremely exceptional situations'?”. As a general objective, we seek to analyze which criteria are handled by the Criminal Chamber of that Court to assign concrete meaning to the undetermined legal concept of “exceptional situations”. This general objective will be improved with the complementary explanation of the following specific objectives: to investigate the systemic aspects associated with the phenomenon of incarceration of women and the causes of the substantial growth; to analyze the arguments that make up the Judgment of the Collective Habeas Corpus nº 143.641/SP and the precedents of relevant judgments regarding the matter emanating from other Courts; and to investigate the criteria used by the Criminal Chamber of the TJ/PB for denying the replacement of preventive detention in house arrest, under the allegation of the existence of “extremely exceptional situations”. This dissertation was developed from the methodological perspective of feminist theory, with an indication of methodological reference in the work of Mendes (2017). Technically, bibliographic and theoretical analysis was carried out in the initial chapters and in the third chapter it was made an documentary research based on a study of TJ/PB precedents, using the method of content analysis in accordance with the procedural propositions of Bardin (2016). The selection of judgments that fall within the scope of this research was carried out by consulting the jurisprudence website of the selected Court, in the period between November 9, 2021, and April 11, 2022, by placing the keyword "HC nº 143641" in the search field. Among the main conclusions reached, we point out the use, by the Criminal Chamber of the TJ/PB, of subjective criteria in order to justify the denials of house arrest to women mothers, with special recourse to the attribution of the meanings of "guarantee of public order”, “crime committed inside the residence” and “no proof of the essential role of the mother for the care of the children”.